Autochthony in the Midst of Afro-pessimism in Chirikure Chirikure’s Poetry - Tembo, Charles; Gijimah, Tevedzerai (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2016)
This article exposes and interrogates Chirikure’s depiction of autochthony. It is an effort towards discussing Chirikure’s social vision which is torn between positive and negative images of Africa. It establishes that a sharp sense of belonging manifests in Chirikure’s poetry but such a sense is clouded by a pessimistic attitude to life which breaks the ability to transform Africans’ lives positively. This effort is energized by the idea that as Eurocentric critics have invested and continue to invest their time and energy in projecting negative images of Africa, Chirikure is committed to challenging the Eurocentric dehumanization of Africa with a view to empower African multitudes. While Chirikure challenges Eurocentric perceptions of Africa which by and large benefit the creators of the stultifying negative images of Africa by crippling Africans’ sense of belonging, such a literary position is obliterated by the stultifying negative images of Africa in some of his selected poems. While Chirikure celebrates indigeneity or autochthony, this sense is clouded by Afropessimism and such a literary position kills the creative force. The rallying point of the article is that negative images of Africa break the spirit to struggle while positive images are developmental and liberating.